A mini review on selenium quantum dots: synthesis and biomedical applications - Huang, Yanhua; Lu, Guangming; Zhou, Li (Frontiers in Bioengineering and Biotechnology, 2023)
In recent years, the demand for advanced biomedical nanomaterials has seen a noticeable surge. Among the essential trace elements in the human body, selenium has gained recognition for its anti-cancer, antioxidant, and immune regulatory properties. However, traditional selenium-based semiconductor quantum dots (QDs) are often comprised of heavy metal elements that tend to be toxic, thereby limiting their usage in biomedical applications. Fortunately, the advent of elemental selenium quantum dots (SeQDs), a new kind of fluorescent nanomaterial with unique physicochemical properties, has provided a solution to this problem. These SeQDs are known for their low toxicity and good biocompatibility, making them a promising candidate for biomedical applications. In this mini-review, we delve into the synthesis methods of fluorescent SeQDs and the latest progress in their applications in bioimaging, biosensing, and diagnosis treatment. Finally, we identify the major challenges and future prospects in the field of SeQDs.